Analisis Perbandingan Rentabilitas (Studi Kasus Bank Mitra Cemawis Mandiri Pada Tahun 2019-2021): Profitability Comparative Analysis (Case Study of Bank Mitra Cemawis Mandiri in 2019-2021) - Sonia Anggraeni; Nugroho Wibowo (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This study analyzes the comparison of the profitability of a bank, there are some financial analyzes that can be used to assess a company, one of them by using the ratio analysis method. The profitability ratio is the assessment of the bank's ability to maintain business operations and capital. Return on equity can be calculated using ROA, ROE, and NPM. The author wants to know how Bank Mitra Cemawis Mandiri effectively uses its capital and uses its assets to generate profits over a certain period for stable business purposes and can cover all debt costs to other parties. Based on the analysis results of the picture of the level of profitability at the Mitra Cemawis Mandiri bank during the 2019-2021 period, the ROA of Bank Mitra Cemawis Mandiri in 2019 is still not healthy because it has not yet reached the BI standard of 5.98%. ROE at Bank Mitra Cemawis Mandiri, in the period 2019 to 2021, is in good health, because during that period the bank can efficiently earn profits and has entered into the standard provisions of BI. The NPM at Bank Mitra Cemawis Mandiri in the 2019 to 2021 period has increased and the bank can say it’s good at making good profits